IMPLEMENTASI MODEL BISNIS CANVAS PADA USAHA BUBUR ORGANIK STUDI KASUS PT. ROFINDIYA EKAMULIA SUKSES - Lidia, Lidia; Triyono, Triyono (GREAT: Jurnal Manajemen dan Bisnis Islam, 2024)
This study aims to find out how to apply the Business Model Canvas with the current Business Business Model Canvas and Future Business Model Canvas organic porridge PT. Rofindiya Ekamulia Sukses. The problem in this study is that the "Bubur Onic" organic porridge business which is a famouse organic porridge in the area has not mapped the business and looked for solutions to retain consumers. The research approach used is a qualitative approach with the type of case study research. The subject of this research is the owner of business "Bubur Onic". In the midst of the increasing number of culinary business competitors who present a more modern concept compared to those businesses that still package their businesses conservatively. The analytical technique used is SWOT analysis to see the weaknesses and threats faced by optimizing the strengths and opportunities they have and mapping the business using the Business Model Canvas (BMC). This type of research is qualitative descriptive research using interview, observation and documentation methods. The results of the study showed customer segments in geographical, demographic and psychographic segment types, Value Propositions with performance, Cuztomization, innovation and owned, Channels via Whatsapp, telephone, website and Facebook, Customer Relations using personal assistence and Co-Creation, Revenu streams from asset sales and bubur pouch services, key resources in the form of physical, intellectual, human and financial. Key activity of production based on orders and marketing activities, key patnership is partnerships, and cost structure in the form of fixes and value costs for value driven.